Challenging diagnosis and treatment of HIT in child with ventricular assistance device. (18th June 2015) - Weintraub, Lauren; Driscoll, Catherine; Aydin, Scott; Lamour, Jaqueline M.; Weinstein, Sam; Manwani, Deepa
Abstract HIT presents the clinician with unique diagnostic challenges, especially in the pediatric population. The HIT clinical sequelae of thrombocytopenia and thrombosis are secondary to the activation of platelets by heparin–antibody complexes. Diagnosis involves clinical observations and confirmatory laboratory testing using antibody detection and the functional SRA. As we describe in the following case of a six‐yr‐old female, the SRA may be difficult to interpret in the case of high‐titer antibodies and illustrates the need for repeat testing in cases of high clinical suspicion.